The Social Construction of School Failure - Schuttloffel, Merylann J. (Education Policy Analysis Archives, 2000)
A case study highlights barriers encountered by an urban school principal in implementing reforms within the context of the Kentucky Educational Reform Act. By comparing the competing expectations of Miller's (1995) five capitals and Ianneconne and Lutz's (1970) dissatisfaction theory, the case study dramatizes that Site-Based Decision-Making councils exemplify a policy decision that ignores the practical realities of distressed schools. The lack of congruence between policies and the school reality makes implementation of school reform predictably unsuccessful.